A Bibliometric Analysis Of Capital Budgeting Strategies: Developments, Trends, and Future Directions - Kumorowati, Indah; Nasrullah, Ahmad Happy; Handayani, Puji; Restuningdiah, Nurika (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the development and trends in research on capital budgeting in Indonesia from 2015 to 2025 using a bibliometric approach. Data were collected through a systematic search of the Scopus database using the keyword “capital budgeting” focused on article titles, abstracts, and keywords. A total of 127 documents meeting the inclusion criteria were analyzed descriptively and visualized using VOSviewer software. The results of the study show a fluctuating publication trend, with the highest peak in 2024. The United Kingdom and the United States are the countries with the largest publication contributions, while Indonesia still shows limited contributions. Co-authorship analysis reveals low connectivity between authors, whereas co-occurrence analysis identifies the keyword “capital budgeting” as the primary hub connecting various topics, including the cost of capital, corporate governance, and NPV. Overlay and density visualizations also reveal that the cost of capital is a relatively new topic with potential for further development. These findings provide a comprehensive overview of the dynamics of capital budgeting research and identify research opportunities that remain open, particularly in Indonesia.